Gene Flow from Genetically Modified Rice to Their Weedy and Wild Relatives and Its Environmental Consequences - Estiati, Amy; Nugroho, Satya (BRIN, 2009)
Rice is one of the most important food crops in the world. Nearly half of the world population consume rice as their staple food (FAO, 2004). With the increasing of world population, the need to provide more food supplies including rice is obvious. Biotechnology is expected to play major roles in the improvement of crop productivity and quality. Unlike transgenic maize, eventhough many research have been done to improve rice performance by genetic engineering, transgenic rice has not been released or commercialized. Among those research to improve rice performance are the attempt to introduce biotic and abiotic stress tolerant traits, herbicide tolerant trait and beta-carotin biosynthetic pathway. Currently, several genetically modified rice cultivars have been and being tested on limited field trials. Undoubtedly, biotechnology will benefit agriculture and thus providing enough food source to keep up with the ever-increasing needs in the future. However, the release and utilization of such technology in agriculture is still arising concerns about the impact to the environment. Therefore the possibility of the transgene escape to the environment needs to be analyzed. For example, whether the application of such technology can create superweed that resulted in the environment problems. On the other hand, cultivated rice may acquire genes for weediness from pollen-mediated gene flow of weedy or wild rice occurring inside or near cultivated rice fields, which leads to persistence and invasiveness of the cultivated rice, although the chance is low. This article discuss the possibility of the occurrence gene flow from the application of genetically modified rice to surrounding rice plants including its wild relatives and weed, and the requirements or precautions needed to be done to prevent gene flow.